Preparation of Spherical Powders by Hydrolyzing Solvent - Guo, Chang-Ping; Cai, Xing-Wei; Lin, Xiang-Yang; Pan, Ren-Ming (Asian Journal of Chemistry, 2012)
Combining the theory of esters hydrolyzing and emulsion solvent extraction method, a new method of making spherical powders by hydrolyzing solvent is developed, aiming at solving the deficiency of traditional preparation process of spherical powders (emulsion solvent evaporation technique). The powders showed a rough spherical surface and narrow size distributions under the condition: the vol./wt. ratios of solvent to NC being 3.5 mL: 1 g, uniform temperature 72 ºC, the volume ratios of 98 % H2SO4 to water being 1:200. The mechanism of hydrolysis reaction was validated by detection of ethanol in the distillation by gas chromatography. Comparing with the traditional process, hydrolyzing technique can shorten the reaction time and decrease the temperature, in addition, it uses constant temperature and the technological process is simplified, which would effectively prevent the softened grains aggregating.